Lithium and the Interplay Between Telomeres and Mitochondria in Bipolar Disorder - Lundberg, Martin; Millischer, Vincent; Backlund, Lena; Martinsson, Lina; Stenvinkel, Peter; Sellgren, Carl M.; Lavebratt, Catharina; Schalling, Martin (Frontiers in Psychiatry, 2020)
Bipolar disorder is a severe psychiatric disorder which affects more than 1% of the world’s population and is a leading cause of disability among young people. For the past 50 years, lithium has been the drug of choice for maintenance treatment of bipolar disorder due to its potent ability to prevent both manic and depressive episodes as well as suicide. However, though lithium has been associated with a multitude of effects within different cellular pathways and biological systems, its specific mechanism of action in stabilizing mood remains largely elusive. Mitochondrial dysfunction and telomere shortening have been implicated in both the pathophysiology of bipolar disorder and as targets of lithium treatment. Interestingly, it has in recent years become clear that these phenomena are intimately linked, partly through reactive oxygen species signaling and the subcellular translocation and non-canonical actions of telomerase reverse transcriptase. In this review, we integrate the current understanding of mitochondrial dysfunction, oxidative stress and telomere shortening in bipolar disorder with documented effects of lithium. Moreover, we propose that lithium’s mechanism of action is intimately connected with the interdependent regulation of mitochondrial bioenergetics and telomere maintenance.